Effects of Contraception Pills and Hormone Replacement Therapy on Tissue Plasminogen Activator -1 and Plasminogen Activator Inhibitor-1 in Per and Postmenopausal Women - Hind Chassab Karam; Dakhel Ghani Omran (Indian Journal of Forensic Medicine & Toxicology, 2021)
Contraception is a program employed to avoid pregnancy during premenopausal period where as hormonereplacement therapy (HRT) is a medical option to ameliorate menopausal complications. The present studywas designed to evaluate the effects of contraceptions and HRT on estradiol hormone ,tissue plasminogenactivator-1 (TPA-1),and plasminogen activator in hibitor-1(PAI-1).One hundred (120) women were recruited ;30 women with contraception; 30 women with HRT ,and60women contraception ; with HRT , and 60 women as a control group. All ages of women were rangedbetween 31-70 years old and subdivided into four groups(31-40,41-50, 51-60, 61-70 years old ).Data obtained from this study indicated a significant elevation (p<0.05) in the levels of estradiol hormone inall tested groups of women compared to control women (without contraception and HRT).It was establisheda significant drop (p<0.05) in the concentration of TPA-1 in women taking contraception and those intakeHRT in a comparison with control groups. About levels of PAI-1,they were significantly higher (p<0.05)in both women with contraception and HRT than of control women .From these observations the availableconclusion may be administration of contraception and HRT influence fibrinolytic system and increaseincidence of thrombotic events .